Adsorption of organic micropollutants onto electrospun nanofiber membranes functionalized with activated carbon. (October 2021) - Soberman, Mark J.; Tabe, Shahram; Farnood, Ramin R.
Abstract: This study provides new insights and a fundamental understanding of the effect of particle size on the structure and performance of electrospun nanofiber membranes (ENMs) containing powdered activated carbon (PAC). PAC was fractionated into four size groups (<20, 32–45, 53–75, 90–125 μm) and incorporated into ENMs made of polyacrylonitrile. Scanning electron microscopy images of ENM samples revealed that PAC particles were covered by a thin and porous layer of PAN. The specific surface area (SSA) of PAC-containing ENMs decreased by increasing PAC particle size and was found to be directly proportional to the exterior surface area of PAC particles. Our findings suggest that only pores located near the surface of PAC were mainly accessible for adsorption. Isotherm studies showed that the Freundlich adsorption capacity for the removal of methylene blue was proportional to the SSA of these membranes and was controlled by pores in the range of 1.3–5.0 nm. Finally, a diffusion-based model was developed that described adsorption kinetics of PAC-containing ENMs. This model corroborated our findings that the pseudo-first order adsorption rate constant was a linear function of SSA of membrane and the inverse of PAC particle size. Graphical abstract: Image, graphical abstract